2008
DOI: 10.1371/journal.pmed.0050101
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prenatal and Childhood Blood Lead Concentrations with Criminal Arrests in Early Adulthood

Abstract: BackgroundChildhood lead exposure is a purported risk factor for antisocial behavior, but prior studies either relied on indirect measures of exposure or did not follow participants into adulthood to examine the relationship between lead exposure and criminal activity in young adults. The objective of this study was to determine if prenatal and childhood blood lead concentrations are associated with arrests for criminal offenses.Methods and FindingsPregnant women were recruited from four prenatal clinics in Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
243
3
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(266 citation statements)
references
References 30 publications
(33 reference statements)
15
243
3
5
Order By: Relevance
“…From a prospective viewpoint, high lead levels in the mother during the first and second trimester of pregnancy are associated with increased risk for arrest for violent crimes in adulthood 24 . High dentine lead levels assessed at ages 6-9 years have been associated with increased violent offending at ages 14-21 years, with poorer cognitive functioning mediating this relationship 25 .…”
Section: Prenatal and Perinatal Influencesmentioning
confidence: 99%
See 1 more Smart Citation
“…From a prospective viewpoint, high lead levels in the mother during the first and second trimester of pregnancy are associated with increased risk for arrest for violent crimes in adulthood 24 . High dentine lead levels assessed at ages 6-9 years have been associated with increased violent offending at ages 14-21 years, with poorer cognitive functioning mediating this relationship 25 .…”
Section: Prenatal and Perinatal Influencesmentioning
confidence: 99%
“…High dentine lead levels assessed at ages 6-9 years have been associated with increased violent offending at ages 14-21 years, with poorer cognitive functioning mediating this relationship 25 . Some studies have carefully controlled for potential confounds such as poverty, maternal smoking, alcohol use, and drug use, and have shown that these findings apply to women as well as men 24,25 . Higher manganese levels in the mother during pregnancy have also been associated with increased externalizing behavior problems (aggressive, destructive, defiant) at age 8-9 years 26 .…”
Section: Prenatal and Perinatal Influencesmentioning
confidence: 99%
“…Lead quantities formerly regarded as trivial are associated with permanent cognitive damage in children [3], including those prenatally exposed [4]. Lead is associated with impaired motor function [5], attentional dysfunction [6], and even criminal behavior [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…17 Antisocial behaviors, including conduct disorder, delinquency, and criminal behaviors, can result from a variety of risk factors, but there is substantial evidence that lead toxicity is 1 of the major risk factors for their development. 16,[19][20][21][22] Needleman et al 16 found that adolescents who had higher bone lead concentrations had higher scores for delinquency and aggression. In a meta-analysis of 16 studies, Marcus et al 22 concluded that lead exposure, measured via blood lead or bone lead concentrations, was a risk factor for conduct disorder.…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…In 2 prospective longitudinal studies, higher childhood blood lead or tooth lead concentrations resulted in higher rates of self-reported delinquent behaviors and arrests or convictions. 20,21 Reyes 23 concluded that the reduction in population mean blood lead concentrations was the major risk factor associated with the decline in severe violent behaviors over the past 3 decades.…”
Section: Scope Of the Problemmentioning
confidence: 99%